Regression models for computing the thermal efficiency of industrial boilers in the Philippines - Dominguez, Raul Q. (2007)
Current methods for determination of the efficiency of boiler or system generating units such as the point-output method and the indirect method, both require the availability of measuring instruments and necessity of carrying out of tedious and comprehensive field measurements or tests. Because of the prohibitive costs and complexities of these activities, boiler efficiency tests are seldom carried out as part of regular boiler maintenance in industrial and commercial facilities. Recognizing this as a major barrier to efficiency improvement , boiler efficiency test are provided by the Philippine Department of Energy (DOE) Consultancy and Engineering Services staff to the industrial and commercial sectors. From the data of DOE, an assessment of the technical and operating parameters of boilers in operation in the country was undertaken. This study took one farther by developing regression models to establish the causal relationship of the boiler efficiency on a number of plant performance indicators and observable parameters. The regression models are useful for predicting the efficiency. Theses can be used in formulating the maximum efficiency benchmarks which eventually can be applied to estimate the impact of boiler efficiency improvement potential to the country. The information generated in the study could provide government decision-makers and other stakeholders with practical insights and information that will be critical for the design and implementation of more receptive policies and programs for advancing boiler efficiency improvement.
"May 2007."
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman.
Keywords: Boilers -- Efficiency; Boilers -- Thermal properties